State Civil Apparatus Neutrality Policy in General Elections: Lessons from Several Countries - Sri Handayani; Albertus Sentot Sudarwanto; Enny Nurbaningsih; Rosalia Agustin Shela Hendrasmara (Contrarius Indonesia, 2026)
This study evaluates the legal framework governing State Civil Apparatus neutrality in Indonesia by examining how recurring neutrality violations, political intervention, ineffective sanctions, and the transfer of supervisory authority under Law Number 20 of 2023 have weakened bureaucratic professionalism and electoral integrity. This study employs normative legal research by applying statutory, conceptual, case, analytical, comparative, and philosophical approaches. It examines primary, secondary, and tertiary legal materials through qualitative legal analysis and draws conclusions using deductive reasoning. The findings demonstrate three major conclusions. First, Pancasila, constitutional principles, and good governance provide the legal and philosophical foundation for State Civil Apparatus neutrality by requiring a professional, impartial, and politically independent bureaucracy. Second, the existing supervisory framework fails to ensure effective neutrality enforcement because institutional dependence, fragmented authority, and conflicts of interest weaken regulatory implementation. Third, this study reconstructs the regulatory framework by establishing an independent supervisory institution, strengthening legal provisions on neutrality, protecting whistleblowers, regulating digital conduct, and integrating administrative and electoral sanctions to improve bureaucratic integrity, strengthen legal certainty, and promote democratic governance.